Yugoslavia: From wars to European integration: Perspectives from university students in Bosnia and Herzegovina, Croatia, Serbia and Kosovo - Sousa, Ricardo Alexandre Encarnação (2016)
What are the conditions for meaningful reconciliation in post-conflict societies? This was the departure research question for this research project focusing on the former Yugoslavia, in particular on the territories of the three largest former republics: Bosnia and Herzegovina, Croatia, Serbia, and Kosovo, due to the latter’s respective specificities. Starting out from a general hypothesis: the fulfilment of a set of political, social and economic conditions fosters and enables tolerant and peaceful coexistence among the peoples of the former Yugoslavia, this then shaped and thus defined the main research objectives: understanding the way in which the post-war educational systems have or have not contributed to reconciliation between the various nations and peoples of the region; the prospects of European integration as an engine for pacification; the role of hate speech formulated in the media and culture and as well as the means of overcoming it. Through research that interweaves with the professional activity of the author – a journalist with extensive experience in coverage of the region – and deploying a combination of qualitative and quantitative methods (a survey answered by over 270 students from the countries under study), this dissertation strives to provide new clues for approaching nationalist phenomena and perspectives (taking into account the responses of students to the survey this thesis put forward) on reconstructing post-conflict societies and furthermore identifying a set of conditions that must first be verified before ever achieving what this dissertation defines as reconcivicnation, a civic reconciliation of nations.